ŠVENTOJO RAŠTO LEIDINIAI VILNIAUS UNIVERSITETO BIBLIOTEKOS XVI AMŽIAUS KNYGŲ FONDUOSE - GRIGONIS, EVALDAS (Knygotyra, 2011)
Vilniaus universiteto bibliotekos Retų spaudinių skyriusUniversiteto g. 3, LT-01122 Vilnius, LietuvaEl. paštas: evaldas.grigonis@mb.vu.ltStraipsnyje analizuojami XVI a. Šventojo Rašto leidiniai, saugomi Vilniaus universiteto bibliotekos Retų spaudinių skyriaus fonduose. Pateikiama statistinės informacijos apie šių spaudinių kalbinį pasiskirstymą, leidimo vietas, kai kurie iš jų nagrinėjami plačiau, žvilgsnį telkiant į vietinius leidėjus, kurių spaustuvėse pasirodė dabar VUB esantys minėto laikotarpio Šventraščiai. Taip pat analizuojami šių knygų nuosavybės ženklai (proveniencijos), remiantis jais aptariamas buvusių LDK vienuolynų ar apskritai vienuolijų (jos buvo dažniausios Biblijos skaitytojos) sąlytis su spausdintiniu Dievo Žodžiu, atkreipiamas dėmesys į nemažos dalies Šventojo Rašto leidinių (jų leidėjų ir komentatorių) sąsajas su protestantizmu.Reikšminiai žodžiai: Šventasis Raštas, Biblija, XVI a., Vulgata, lotynų kalba, Vilniaus universiteto biblioteka, nuosavybės įrašai, Lietuvos Didžioji Kunigaikštystė, Katalikų bažnyčia, vienuolynai, Reformacija Europoje, draudžiamųjų knygų sąrašai, leidėjai, spaustuvininkai, iliustracijos.PUBLICATIONS OF THE HOLY SCRIPT IN THE BOOK COLLECTIONS OF THE 16TH CENTURY AT VILNIUS UNIVERSITY LIBRARYEVALDAS GRIGONISAbstractThe Holy Script has already lost its special significance to an ordinary Western man in modern times, although since the entrenching of Christianity in the 4th century A.D. the Holy Script was for long centuries the main cultural text of the European civilization. No wonder the first printed book from which the era of the printed word began in the culture of the world was the so-called 42-Line Bible of J. Gutenberg (in Latin, published in c. 1456).There are in total 149 pieces (or separate parts) of the Bible in the Vilnius University Library, issued between 1501 and 1600. The majority of these editions were published in Latin (70% of the Bibles), so it is natural that in the 16th century the printed Latin Bible (Vulgate) experienced its age of flowering in Europe (in total, 438 editions of Vulgate were issued ). The path of the Holy Scripture to the former Grand Duchy of Lithuania (GDL) varied from such Catholic countries as France (the latter “presented” the bulk – over 25% – of Bibles kept at the Vilnius University Library from the 16th century), Belgium, Poland, Italy, Austria to such a “heretical” land as England, or such Protestant towns as Geneva, Basel, Strasbourg, Zurich and quite a few towns of Lutheran Germany such as Nuremberg, Frankfurt am Main, Leipzig, Rostock, etc. There is also the Holy Script published in the GDL – the famous Brest (or Radvila) Bible (issued in 1563). The wide geography of the publications’ origin as well as the miscellaneous (from the point of view of confessions) cast of Bibles’ editors, commentators, translators or publishers raises certain questions about the existence of ecclesiastical discipline in the GDL, for in accordance with various Indices librorum prohibitorum (Indexes of Prohibited Books), which were obligatory for Catholics, almost 46% of the 16th-century Holy Scriptures in the present Vilnius University Library were forbidden to be used at one time. On the other hand, the markings of ownership (provenances) in these books show that of all the 16th-century Bibles kept at the Vilnius University Library, which have such markings (91 copies), even over ¾ for some time belonged to monasteries, Catholic churches and colleges. Furthermore, more than half of private owners consisted of Catholic clergy and monkery. Talking of separate monasteries, the provenances also indicate that the majority of the 16th-century Bibles found their way to the Vilnius University Library from the Grodno Dominicans; the most affluent “donors”among monkhood were Franciscans (including both Observants and Conventuals). These findings, though indirectly, indicate the influence of Western and Central Europe on the religious life of the 16th-century GDL through the Holy Script – the fundamental writing for Christians.